CRIMINALIZING MARITAL RAPE AS A HUMAN RIGHTS OBLIGATION UNDER INTERNATIONAL LAW: A CRITICAL APPRAISAL OF INDONESIA’S LEGAL FRAMEWORK - Iswara, Rizka (Indonesian Law Journal, 2025)
Marital rape is a form of gender-based violence that is often hidden yet widely prevalent. This article critically examines the Indonesian legal framework in responding to the issue of marital rape, emphasizing the importance of criminalization as a state obligation to meet international human rights standards. Through a normative juridical approach and comparative legal analysis, this article examines the gap between national regulations and international provisions. It was found that despite normative progress, such as the recognition of sexual violence within marriage through national legal reforms. This paper recommends strengthening national criminal law norms through the explicit criminalization of marital rape and the harmonization of national regulations with international human rights standards as a form of the state's commitment to fulfilling its international obligations.